KEANEKARAGAMAN HAYATI INDONESIA Suatu Tinjauan : Masalah dan Pemecahannya - Sutoyo Sutoyo (Universitas Tribhuwana Tunggadewi, 2010)
Biodiversity is a term that covers all forms of life including genes, species of plants, animals, microorganisms and ecosystems and ecological processes. Economic use of biodiversity are still oriented towards large profits without regard to environmental damage. Explore the flora and fauna species can lead to excessive scarcity and extinction of species, so that natural resources can not support human welfare. Indonesia is one country that has the richest tropical forests in the world. Tropical forests as a storehouse of biodiversity is alleged to have shrunk by more than half, even agricultural land has been degraded, both in quality and quantity. In an effort to conserve biodiversity in Indonesia is practically encouraging the process of ecological succession to create a heterogeneous environment that provides opportunities of all species can evolve naturally. These efforts by establishing a nature reserve area, conservation of natural resources include: land, water, plants and animals, conservation germplasm, land and crop rotation, and the socialization role and function of biodiversity. Support of science and technology is needed as a tool in monitoring the sustainable utilization of biological resources, and policies and legal instruments. by way of identification and inventory of biological diversity in the distribution, presence, utilization, and management systems